(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Antioxidants are one of the most important nutraceutical compounds that have emerged from the recent decades of research in food science. The advances in this field have allowed a better understanding of the free radical damage of cellular constituents, such as lipids, proteins and DNA. Antioxidants and radical scavengers have a crucial role in the treatment or prevention of several diseases such as type 2 diabetes, atherosclerosis, cancer, cardiovascular disorders and neurodegenerative disorders. Restrictions on the use of synthetic antioxidants are being imposed because of their toxic properties. The present study is the continuation of a program aimed at investigation on antioxidant activity of extracts from medicinal plants and to identify alternative natural and safe sources of food antioxidant especially from plant origin. In this report the anti-peroxidative effect of alcoholic extract of Murraya koenigii and Cinnamomum tamala have been studied in rat liver homogenate where ferrous sulphate has been used as inducer to induce lipid per oxidation. On the basis of results, it could be concluded that TBARS production in normal condition group is very slow and it is very high in FeSO4 treated groups. Results further revealed that at lower doses, the rate of formation of TBARS is slow but grows as the level of dose is increased. Significant and moderate results were found from 0.40 mM to 0.80 mM of ferrous sulphate. The mechanisms underlying the beneficial effects may be related to the antioxidant effects of the polyphenols resulting in decreased free radical production.